2022
DOI: 10.2196/27791
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Cognitive Behavioral Therapy in e–Mental Health Apps: Literature Review

Abstract: Background To address the matter of limited resources for treating individuals with mental disorders, e–mental health has gained interest in recent years. More specifically, mobile health (mHealth) apps have been suggested as electronic mental health interventions accompanied by cognitive behavioral therapy (CBT). Objective This study aims to identify the therapeutic aspects of CBT that have been implemented in existing mHealth apps and the technologies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 85 publications
1
13
0
2
Order By: Relevance
“…This is in contrast to a previous mindfulness intervention study conducted on palliative caregivers in 2016 in which 90% of interventions were provided face-to-face [32]. Interventions using digital devices are accessible at any time and place, making them tremendously advantageous for cancer caregivers, who have a sizable temporal burden [33]. In our review, the participants of two studies using mobile applications [20,29] positively evaluated the intervention based on its ease of access.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is in contrast to a previous mindfulness intervention study conducted on palliative caregivers in 2016 in which 90% of interventions were provided face-to-face [32]. Interventions using digital devices are accessible at any time and place, making them tremendously advantageous for cancer caregivers, who have a sizable temporal burden [33]. In our review, the participants of two studies using mobile applications [20,29] positively evaluated the intervention based on its ease of access.…”
Section: Discussionmentioning
confidence: 95%
“…One notable disadvantage of interventions using digital devices is that they imply less interaction with the therapist. Cognitive-behavioral therapy, which values the relationship with the therapist, still lacks su cient evidence regarding mobile or web-based interventions that do not require the user to communicate directly with the therapist [33]. Two interventions using the web page and the mobile app without interactions with the therapist failed to demonstrate effectiveness on caregivers [20,29], except for a positive effect in the domain of mindfulness [29].…”
Section: Discussionmentioning
confidence: 99%
“…In such platforms, advice on daily physical or mental behavior, such as diets, activities and treatments, are suggested to the users. Eventually, the daily functioning of the user is monitored, and personalized reports are delivered [67][68][69][70][71].…”
Section: Social Media's Impact On Health Care Systemmentioning
confidence: 99%
“…In particular, fully automated mental health apps (apps without human support) can potentially support healthcare professionals' workloads (Richards et al, 2018). However, although some researchers suggested that smartphone apps are efficient in managing mental health problems (Ebert et al, 2018; Firth et al, 2017), other researchers pointed out that the effect sizes are relatively moderate and there is no convincing evidence of the efficacy of mental health apps related to the clinical outcomes (Denecke et al, 2022; Goldberg et al, 2022). Consequently, understanding how fully automated mental health apps can be designed to bring better clinical outcomes is critical to improving service delivery, clinical workflows and patient care.…”
Section: Introductionmentioning
confidence: 99%